Immune checkpoint inhibitors in malignancies after liver transplantation: A systematic review and pooled analysis. (27th September 2022) - Kayali, Stefano; Pasta, Andrea; Plaz Torres, Maria Corina; Jaffe, Ariel; Strazzabosco, Mario; Marenco, Simona; Giannini, Edoardo G.
Abstract: Background and aims: Treatment of de novo malignancies and recurrent hepatocellular carcinoma with immune checkpoint inhibitors (ICI) in liver transplant recipients (LT) is an attractive strategy that is infrequently pursued because of the lack of strong evidence regarding their safety and efficacy. In this systematic review with pooled analysis, we aimed to assess safety and efficacy of ICI therapy following LT. Methods: We performed a systematic search of case reports and series published until January 2022. We included 31 publications reporting a total of 52 patients treated with ICIs after LT and assessed in a pooled analysis the risk of graft rejection and the outcome of ICI therapy. Results: Acute graft rejection occurred in 15 patients (28.8%) and 7 patients (13.4% of the total cohort) died because of graft loss. Rejection was associated with shorter overall survival (OS) (17.2 months, confidence interval [CI] 12.1–22.2 vs. 3.5 months, CI 1.6–5.4, p < 0.001). Disease control rate was 44.2% ( n = 23), and in these patients, OS was longer than in non‐responders (26.4 months, CI 20.8–32.0 vs. 3.4 months, CI 2.1–4.7, p < 0.001). Conclusions: Observational, off‐label experience suggests that treatment with ICI for advanced malignancies in LT recipients might not be discarded a priori. This notwithstanding, ICI treatment in these patients is associated with a substantial risk of graft rejection and mortality. Prospective studies are needed to provide adequate safety and efficacy figures of ICI treatment in this fragile population.